Proposed Digital Marketing And Customer Relationship Strategy To Increase Brand Awareness And Customer Satisfaction For Cathodic Protection Company - Aufa, Ahmad; Furinto, Asnan (Fakultas Ekonomi Universitas Gresik, 2023)
PT. Dins Pratama Abadi, was established in 2012 as a company focusing on specialty areas of anti-corrosion, marine accessories & geomaterials. The company cooperates with various national companies and government agencies in multiple forms of work according to the company's area of expertise. PT Dins Pratama Abadi is a supplier of cathodic protection products and installations in Indonesia. The company today must contend with shifting markets within the industry. A continual emphasis on rebuilding businesses and services strategy is the approach taken to adapt to this transformation. This research aims to determine the best digital marketing strategy and customer relationship strategy for the PT. Dins to increase and retain customers which is necessary for brand awareness and customer satisfaction improvement which comprise this research. To complete the analysis methodically, various data and aspects will be used to specify the best digital marketing strategy for PT Dins Pratama Abadi. Porter's Five Forces and Customer Analysis were utilized for the external analysis. Additionally, Marketing Mix 7Ps, VRIO Analysis, and STP Analysis were utilized to conduct the company’s internal analysis. In this study, qualitative approach were employed by interviewing five customers of the company who works in different companies to understand the customer’s perspective and decision-making process. The result will be analyzed through SWOT Analysis and Five A’s Customer Journey Framework to develop and proposed the most efficient digital marketing and customer relationship strategy for PT. Dins Pratama Abadi